Assignment of tasks to machines under data replication with a tie to Steiner systems - Wojciechowski, Paweł; Kasprzak, Marta (Zielona Góra: Uniwersytet Zielonogórski)
In the paper a problem of assignment of tasks to machines is formulated and solved, where a criterion of data replication is used and a large size of data imposes additional constraints. This problem is met in practice when dealing with large genomic files or other types of vast data. The necessity of comparing all pairs of files within a big set of DNA sequencing results, which we collected, maintained, and analyzed within a national genomic project, brought us to the proposed results.
Keywords: task assignment; genomic data processing; integer linear programming; Steiner system; heuristic algorithms